Web-based instruments for national competences of physical education teachers - Suroto Suroto; Bayu Budi Prakoso; Anung Priambodo; Fifukha Dwi Khory; Vega Candra Dinata (LPMPP Universitas Negeri Yogyakarta, 2022)
Several studies believe that the use of national standards as a benchmark for teacher quality can align education services to achieve national goals. In addition, the number of years of teaching experience can determine teacher productivity during the course of their profession. This article explores the results of developing a teacher competency measurement instrument based on the Indonesian national standards, and evaluating teacher competency based on gender, grade, and working period. A total of 277 Physical Education (PE) teachers participated in an online survey via the web http://risetpjokindonesia.com/ to measure teacher competency. The measurement results were analyzed using confirmatory factor analysis and Cronbach's alpha to test validity and reliability. T-test and one-way ANOVA were used to evaluate teacher competency based on gender, grade, and working period. The findings show that the measurements made are valid and reliable, so they can be used for similar measurements in the future. Gender, grade, and working period were found to affect teacher competency. The development of teacher competency based on working period provides input in the form of accuracy of the teacher professional development carried out and the limitation of the productive period of the teacher in carrying out his or her profession.